International Trade Outlook for Latin America and the Caribbean 2021 - Economic Commission for Latin America; the Caribbean (United Nations, 2022)
This edition of International Trade Outlook for Latin America and the Caribbean covers 2021 reviews the recent performance of global and regional trade following the crisis caused by the coronavirus disease (COVID-19) pandemic. The pandemic triggered a significant loss of export capacity in the region, affecting micro, small and medium-sized enterprises in particular. The COVID-19 pandemic has underscored the strategic nature of this industry, not only because of its direct link to public health, but also because it is an innovative sector with significant technological externalities.